Analisis FaktorPenyebab Contract Change Order pada Proyek Jalan menggunakan SWOT - Muhammad Fadli; Indra Farni (Institut Teknologi Garut, 2025)
This study aims to analyze the factors causing Contract Change Orders (CCOs) in road construction projects, focusing on a case study of the Pasar Baru – Alahan Panjang road improvement project in West Sumatra. CCOs often arise due to discrepancies between the initial plan and conditions in the field, such as changes in weather, unexpected soil conditions, and regulatory changes. This study uses a combination of quantitative and qualitative methods, where data is collected through questionnaires and analyzed using SWOT techniques and internal-external factor analysis. The findings of this study indicate that the main causes of CCO in this project are errors in planning, lack of coordination between related parties, and unexpected changes in field conditions. The impacts of CCO include increased costs, delays, and reduced work quality. As a solution, this study suggests the implementation of better mitigation strategies, such as more careful planning, strengthening coordination between parties involved, and more efficient risk management. These findings can be used as a reference in planning road projects that are more adaptive to contract change risks.